The Synergistic Effect of PARP Inhibitors and Immune Checkpoint Inhibitors. (February 2021) - Wu, Zhaozhen; Cui, Pengfei; Tao, Haitao; Zhang, Sujie; Ma, Junxun; Liu, Zhefeng; Wang, Jinliang; Qian, Yuanyu; Chen, Shixue; Huang, Ziwei; Zheng, Xuan; Huang, Di; et al.
Poly (ADP-ribose) polymerase (PARP) inhibitors have demonstrated great promise for treating cancers with homologous recombination (HR) defects, such as germline BRCA1/2 mutation. Further studies suggest that PARP inhibitors (PARPi) can also exhibit efficacy in HR-competent cancers, by amplifying the DNA damage and inducing immunogenic cell death, and PARPi lead to increasing tumor neoantigen, upregulation of interferons and PD-L1, and modulation of the tumor microenvironment, which may facilitate a more profound antitumor immune response. Immune checkpoint inhibitors (ICIs) targeting PD-1/PD-L1 or CTLA-4 have achieved impressive success in the treatment of different malignancies. However, only a subset of populations derive clinical benefit, and the biomarkers and resistance mechanisms are not fully understood. Therefore, given that PARPi could potentiate the therapeutic effect of ICIs, PARPi combined with ICIs are becoming an alternative for patients who cannot benefit from ICI monotherapy. In this review, we focus on the mechanisms and immune role of PARPi and discuss the rationale and clinical studies of this combined regimen.